2020
DOI: 10.1002/jez.2388
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulation and thermal performance of crested geckos (Correlophus ciliatus) suggest an extended optimality hypothesis for the evolution of thermoregulatory set‐points

Abstract: Crested geckos (Correlophus ciliatus, formerly Rhacodactylus ciliatus) were rediscovered in New Caledonia 25 years ago and despite being common in the pet trade, there is no published information on their physiology. We measured thermoregulation (preferred body temperature, thermal set‐point range, and voluntary limits) and performance (thermal performance curves [TPC] for 25 cm sprint speed and 1 m running speed) of adult and juvenile crested geckos in the laboratory to describe their thermal tolerances, diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…Thermal preferences in two species of racerunner lizards (genus Eremias ) were higher in adults than in juveniles (Tang et al, 2013; Xu & Ji, 2006). In contrast, no difference in T pref was observed between adults and juveniles of the six‐lined racerunner ( Aspidoscelis sexlineatus ; Paulissen, 1988) and no differences in thermoregulatory behaviors or thermal performance curves for sprint speed were found between juvenile and adult crested geckos ( Correlophus ciliates ; Aparicio Ramirez et al, 2020).…”
Section: Ontogenymentioning
confidence: 98%
“…Thermal preferences in two species of racerunner lizards (genus Eremias ) were higher in adults than in juveniles (Tang et al, 2013; Xu & Ji, 2006). In contrast, no difference in T pref was observed between adults and juveniles of the six‐lined racerunner ( Aspidoscelis sexlineatus ; Paulissen, 1988) and no differences in thermoregulatory behaviors or thermal performance curves for sprint speed were found between juvenile and adult crested geckos ( Correlophus ciliates ; Aparicio Ramirez et al, 2020).…”
Section: Ontogenymentioning
confidence: 98%
“…That traits interact to shape evolutionary patterns is exemplified in the “extended optimality hypothesis” for the evolution of thermal set‐points proposed by Aparicio Ramirez et al (2020). In this study, the optimum temperature for sprint performance in crested geckos ( C. ciliatus ) far exceeded PBT and instead corresponded to the maximum temperature tolerated.…”
Section: Contemporary Evolution Shapes Thermal Traitsmentioning
confidence: 96%
“…Perhaps unsurprisingly, free‐living stages that primarily differ only in size can have similar thermal biology. For example, Aparicio Ramirez et al (2020) found no difference in PBTs or thermal performance curves between juvenile and adult crested geckos ( Correlophus ciliatus ) despite individuals differing in size by an order of magnitude. Similarly, Ginal et al (2020) demonstrate similar thermal performance curves for running/swimming between aquatic adult and tadpole African clawed frogs ( Xenopus laevis ) despite differences in both size and morphology.…”
Section: Thermal Limits May Change Across Ontogenymentioning
confidence: 99%
“…CT MAX , and the voluntary maximum temperature (VT MAX ; max T b ) correlates closely with CT MAX resulting from selection to maintain high organismal performance (Aparicio Ramirez et al, 2020;Camacho et al, 2018;Martin & Huey, 2008). When exposed to a novel oxygen environment, the body temperatures selected by an animal should indicate their perception of how the oxygen environment affects thermal performance.…”
Section: Lizards Typically Prefer Body Temperatures (T B ) a Few Degr...mentioning
confidence: 99%
“…Thermoregulatory behavior provides insights into how organisms perceive the thermal environment and can be used to assess the impact of varied environmental conditions on thermal tolerance. Lizards typically prefer body temperatures (T b ) a few degrees below CT MAX , and the voluntary maximum temperature (VT MAX ; max T b ) correlates closely with CT MAX resulting from selection to maintain high organismal performance (Aparicio Ramirez et al, 2020; Camacho et al, 2018; Martin & Huey, 2008). When exposed to a novel oxygen environment, the body temperatures selected by an animal should indicate their perception of how the oxygen environment affects thermal performance.…”
Section: Introductionmentioning
confidence: 99%